Food runner mobile application for UiTM Tapah students / Nur Aishah Baharudin ... [et al.] - Baharudin, Nur Aishah; Zulkifli, Zalikha; Abdul Latif, Lily Marlia; Ahmad, Samsiah; Mohamed Hatim, Shahirah (Universiti Teknologi MARA, Perak, 2021)
Nowadays, people are more convenience to order food online, especially for the university students, who often have a hectic schedule with assignments, presentations, exams and club activities. Universiti Tekonologi MARA (UiTM) Tapah Campus is located in a rural location, which hindering the students to utilize food delivery apps because the area is outside of delivery range supported by the existing food delivery apps. Therefore, this study aims to develop a mobile application that provides a food delivery service for students by students in UiTM Tapah campus. Named as EAT UiTM Tapah, the food runner mobile application was developed with real-time order status notification. Besides faster delivery, this application would allow students to earn extra money by becoming a runner of the food delivery rather than just being a customer. Based on the Waterfall model of System Development Life Cycle (SDLC), this mobile app has been developed on Android platform by using Android Studio and Firebase. This paper provides the fundamental design and implementation of the EAT UiTM Tapah, that was expected to be useful for the students.